Laughter in the puerperium - Curioso Chávez, María del Carmen (2013)
The present article tries to show emotional characteristics being experienced by postpartum women, including that stands out in this article: Laughter. After about forty weeks of gestation and the expectation of a new stage of life. with a new being, we can observe in the postpartum extreme emotions ranging from laughter to tears.